Home-based exercise therapy for treating non-specific chronic low back pain - Kanas,Michel (2018)
SUMMARY OBJECTIVE To evaluate pain, functional capacity, and quality of life of patients with non-specific chronic low back pain, after home-based exercise therapy with different kinds of supervision. METHOD Thirty individuals of both gender, between 18 and 65 years old, performed the proposed exercises three times a week, for eight weeks. Group A (N = 17) performed the exercises after a single supervised session. Group B (N = 13) was supervised once a week at the rehabilitation center. Both groups received a booklet with instructions, and questionnaires to evaluate pain, functional capacity and quality of life; during the initial evaluation, after four and eight weeks. RESULTS There was an improvement in pain and functional capacity between the initial evaluation and week 4, and the initial evaluation and week 8 in both groups (p <0.05). In the quality of life evaluation, the criteria for pain, functional capacity, and physical aspects had significant improvement after 8 weeks (p <0.05). There was no difference when comparing groups A and B (p >0,05). CONCLUSION Home-based exercise therapy, when performed in a period of eight weeks, using the booklet, was effective for improving level of pain, functional capacity, and quality of life in patients with non-specific chronic low back pain. The weekly supervision did not significantly influence the final outcome between the groups.